2016
DOI: 10.1038/am.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Mobility enhancement of strained Si transistors by transfer printing on plastic substrates

Abstract: Strain engineering has been utilized to overcome the limitation of geometric scaling in Si-based thin-film transistor (TFT) technology by significantly improving carrier mobility. However, current strain engineering methods have several drawbacks: they generate atomic defects in the interface between Si and strain inducers, they involve high-cost epitaxial depositions and they are difficult to apply to flexible electronics with plastic substrates. Here, we report the formation of a strained Si membrane with ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…It is speculated that the increase in photoresponsivity was due to the combined effects of the enhancement in optical absorption and photoinduced charge carrier mobilities at elevated strain levels. It is theoretically reported that strain can substantially influence the band edges of optical absorption owing to the change in the symmetry of wave functions and the optical matrix element ( 12 , 15 ), and mobilities of both the charge carriers increase under the strain-induced modification in effective masses and reduction in phonon scattering ( 14 , 16 ). With the increase in applied biaxial strain, the fabricated MSM devices exhibited photosensing beyond the fundamental photoabsorption limit of Si (~1100 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is speculated that the increase in photoresponsivity was due to the combined effects of the enhancement in optical absorption and photoinduced charge carrier mobilities at elevated strain levels. It is theoretically reported that strain can substantially influence the band edges of optical absorption owing to the change in the symmetry of wave functions and the optical matrix element ( 12 , 15 ), and mobilities of both the charge carriers increase under the strain-induced modification in effective masses and reduction in phonon scattering ( 14 , 16 ). With the increase in applied biaxial strain, the fabricated MSM devices exhibited photosensing beyond the fundamental photoabsorption limit of Si (~1100 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, under the influence of tensile strain, the increase in lattice spacing and change in crystal symmetry provide a pronounced shift in the energy band edges of Si, thereby leading to a decrease in the bandgap and an increase in the effective masses of charge carriers ( 13 , 14 ). The reduction in optical bandgap can provide an opportunity to capture photons with energies less than the fundamental bandgap of Si ( 15 ), and the increase in the effective masses can lead to an increase in carrier mobility ( 14 , 16 ). Many theoretical and experimental studies have been conducted to investigate the effect of strain on the band structure of bulk and other low-dimensional systems of Si such as nanowires ( 16 ), nanocrystals ( 17 ), and nanomembranes (NMs) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high‐speed switching and outstanding reliability might be attributed to the excellent interfaces between the Si channel and SiO 2 dielectrics grown by thermal oxidation . The BOX layer beneath the Si channel protects the device from charge‐trapping and roughness effects, which obstruct the carrier transport from the polymeric adhesive (Figure S3a–d, Supporting Information) . The output characteristics (Figure b) display a reasonable ohmic contact property because the doping concentration is well‐controlled by the ion‐implantation process prior to the transfer.…”
Section: Resultsmentioning
confidence: 99%
“…The method has contributed to the development of various applications in high-performance electronics [ 74 , 75 , 76 ], stretchable displays [ 45 ], tactile sensors [ 11 , 12 , 13 , 51 , 77 , 78 ], and biomedical devices [ 79 , 80 ]. Various methods have been investigated for the development of ultrathin single crystalline silicon-based electronics, such as the selective removal of buried oxide using HF [ 78 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ], the bottom etching of silicon substrates using aqueous alkaline solutions of potassium hydroxide (KOH) [ 97 ] or tetramethylammonium hydroxide (TMAH), and removal processes using defined ribbon patterns with bridges using reactive ion etching (RIE) [ 45 , 98 , 99 ]. Conventional electronic devices fabricated using the CMOS (complementary metal–oxide semiconductor) microfabrication processes have drawbacks (e.g., not flexible, fragile in mechanical shock) originating from mechanical properties of bulk silicon, whereas the devices based on ultrathin single crystalline silicon could be mechanically flexible and robust while benefiting from the excellent electrical properties of bulk silicon.…”
Section: Novel Materialsmentioning
confidence: 99%